2023
DOI: 10.3389/fvets.2023.1158588
|View full text |Cite
|
Sign up to set email alerts
|

An overview of carbapenem-resistant organisms from food-producing animals, seafood, aquaculture, companion animals, and wildlife

Abstract: Carbapenem resistance (CR) is a major global health concern. CR is a growing challenge in clinical settings due to its rapid dissemination and low treatment options. The characterization of its molecular mechanisms and epidemiology are highly studied. Nevertheless, little is known about the spread of CR in food-producing animals, seafood, aquaculture, wildlife, their environment, or the health risks associated with CR in humans. In this review, we discuss the detection of carbapenem-resistant organisms and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 159 publications
0
7
0
Order By: Relevance
“…The increasing occurrence of E. coli with bla NDM‐5 in Europe suggests that there is an ongoing global expansion of certain E. coli STs carrying this gene, and that this is now a significant concern in EU/EEA countries (ECDC, 2023a ). Based on nucleotide similarity between plasmids carrying CP‐encoding genes in human and food‐producing animal sources, it has been suggested that specific plasmids have been circulating among E. coli in different species, possibly increasing the risk of zoonotic transmission of carbapenem resistance (Ramírez‐Castillo et al., 2023 ). However, further studies including epidemiological and genetic analyses are required to elucidate the transmission dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing occurrence of E. coli with bla NDM‐5 in Europe suggests that there is an ongoing global expansion of certain E. coli STs carrying this gene, and that this is now a significant concern in EU/EEA countries (ECDC, 2023a ). Based on nucleotide similarity between plasmids carrying CP‐encoding genes in human and food‐producing animal sources, it has been suggested that specific plasmids have been circulating among E. coli in different species, possibly increasing the risk of zoonotic transmission of carbapenem resistance (Ramírez‐Castillo et al., 2023 ). However, further studies including epidemiological and genetic analyses are required to elucidate the transmission dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…CP‐producing Enterobacterales have not only been reported among isolates collected in the harmonised EU monitoring (Bortolaia et al., 2021 ; Carfora et al., 2022 ; Diaconu et al., 2020 ; EFSA and ECDC, 2023 ; Garcia‐Graells et al., 2020 ), but also from companion animals (Ramírez‐Castillo et al., 2023 ; Rincon‐Real & Suárez‐Alfonso, 2022 ), food‐producing animals and derived meat, seafood and vegetables (Brouwer et al., 2018 ; Irrgang et al., 2019 ; Irrgang et al., 2020 ; Köck et al., 2018 ; Liu et al., 2018 ; Ramírez‐Castillo et al., 2023 ; Slettemeås et al., 2017 ; Touati et al., 2017 ; Zurfluh et al., 2015 ). Carbapenems are not authorised for use in animals in the EU, and spill‐over from CP‐encoding genes and/or bacteria from humans has been suggested as a potential source of CP‐producers in the food production (Irrgang et al., 2020 ; Madec et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of ESBLs, and in particular CTX-M-15, in animals has previously been linked to the human sector before it was also detected in animals and the environment [ 30 ]. Additionally, ceftiofur, a third-generation cephalosporin, is the main cephalosporin used in veterinary medicine due to its effectiveness in treating bacterial infections in food-producing animals; for this reason, these antibiotics could provide selection pressure that favors co-selection of plasmids carrying mobile genes (transposon, integron, cassette gene) that result in carbapenem-resistant (CR) strains [ 31 , 32 ]. Here, we identified a CTX-M-15 producing E. coli ST1706, an ST that has previously been described in Japan from different pig farms [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical use of these antibiotics is presently at risk due to the global proliferation of β-lactamases (BLs) with the ability to degrade them, and the increase in the worldwide emergence of carbapenem-resistant organisms (CROs), which constitute a critical growing public health threat [ 34 ]. In livestock or veterinary fields, carbapenems are not licensed and have no legal indication, so their use is prohibited [ 32 , 35 , 36 ]. Nevertheless, many studies conducted in Algeria have reported CROs in livestock, companion animals, and birds [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%